Papaya fruits extracts enhance the antioxidant capacity and modulate the genotoxicity and oxidative stress in the kidney of rats fed ochratoxin A-contaminated diet - Aziza A. El-Nekeety, Khaled G. Abdel-Wahhab, Sekena H. Abdel-Aziem, Fathia A. Mannaa, Nabila S. Hassan, Mosaad A. Abdel-Wahhab (Journal of Applied Pharmaceutical Science, 2017)
Ochratoxin A (OTA) is a mycotoxin widespread contaminates food and has potent nephrotoxicity. The present study aimed to determine total phenolics and DPPH radical scavenging activity for water and ethanolic extracts (WE and EE) of papaya fruits and evaluation of the protective role of these extracts against OTA-induced oxidative damage and nephrotoxicity in rats. Sixty male Sprague-Dawley rats were divided into six groups and treated for 21 days as follow: the control group, OTA-treated group (3 mg/kg diet), WE or EE extracts treated groups (250 mg/kg b.w) and OTA plus WE or EE-treated groups. Blood and kidney samples were collected for different biochemical, cytogenetical and histological analyses. The results showed that WE and EE contained 408.54 and 296.85 g/kg total phenolic, respectively and DPPH radical scavenging activity was higher in WE than EE. Animals fed OTA-contaminated diet showed signs of toxicity as indicated by the significant decrease in body weight gain and food intake, the disturbances in kidney biochemical indices, increase DNA fragmentation and oxidative stress markers, the decrease in antioxidant enzymes activities and gene expression as well as severe histological and histochemical changes in the kidney tissues. Both extracts succeeded to counteract these alterations and WE was more effective than EE. These results concluded that papaya fruits extracts succeeded to a great extant to counteract the oxidative stress of OTA and to protect the kidney against its toxic effects and may be promising candidate as food supplement for the protection against OTA in high endemic area.
Keywords: Ochratoxin A, mycotoxins,kidney,oxidative stress, cytotoxicity,papaya.